KEMATIAN YANG TERJADI LAMA SETELAH SERANGAN: MORTALITAS TERTUNDA (DELAYED MORTALITY) DAN BATAS TEMPORAL PEMBUNUHAN - Zul Khaidir Kadir (Jurnal Riset Multidisiplin Edukasi, 2026)
Research on homicide causation often assumes a short interval between injury and death, leaving delayed mortality insufficiently explained when complications, medical intervention, or pre-existing vulnerability alter the final mechanism of death. This study examines how the temporal boundary of homicide should be determined when death occurs long after the initial attack. It employs a literature-based study combining doctrinal legal analysis with limited functional comparison of legislation, judicial decisions, medical guidance, and scholarly literature from England and Wales, the United States, and Indonesia. The findings show that elapsed time does not sever causation by itself, although a longer interval increases evidentiary uncertainty and the possibility of competing causes. The abolition of the year-and-a-day rule has shifted legal analysis from a fixed calendar limit toward case-specific causal examination, while procedural safeguards remain necessary in unusually delayed prosecutions. The study develops causal persistence as an analytical device for assessing whether the initial injury continues to contribute to death despite changes in the immediate medical mechanism. Complications, medical treatment, withdrawal of life support, and victim vulnerability do not automatically break causation; their legal effect depends on whether they remain connected to the condition created by the attack or provide an independent explanation for death. Delayed mortality may therefore remain attributable as homicide when clinical records, forensic findings, and expert evidence support a coherent causal account. The temporal boundary is reached when the contribution of the initial injury can no longer be established as a real and legally significant part of the fatal outcome.